DETERMINANTS OF EMPLOYEE PRODUCTIVITY AT BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA MANADO - Melisa Rorimpandey; Marjam Mangantar; Regina Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Abstract: The purpose of this study is to determine whether motivation, communication, work stress, job satisfaction, and work-life balance affect employee productivity in the Badan Kepegawaian dan Pengambangan Sumber Daya Manusia Kota Manado. This research uses a quantitative approach with a descriptive research design. The data analysis method used in this research is Multiple Linear Regression Analysis. The researcher distributed questionnaires, and the sample used was 54 respondents. The results of motivation, communication, work stress, job satisfaction, and work-life balance simultaneously have a significant effect on employee productivity in Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Manado. Partially, communication, work stress, job satisfaction, and work-life balance have a significant effect on Employee productivity, while motivation doesn't have a significant effect on Employee Productivity. Based on the results, communication, work stress, job satisfaction, and work-life balance have a substantial effect on employee productivity, although motivation does not. Leaders should consider focusing on the variables that have a significant influence in employee productivity.   Keywords: motivation, communication, work stress, job satisfaction, work-life balance and employee productivity